SISTEM PENGELOLAAN ARSIP PADA SEKRETARIAT JENDERAL KEMENTERIAN PEKERJAAN UMUM DAN PERUMAHAN RAKYAT SUMATERA BARAT - Meilina, Susiyanti; Argonanto, Ari (Ensiklopedia Sosial Review, 2021)
One of the efforts to support the management of archives in the field of the General Bureau at the Secretariat General of the Ministry of Public Works and Public Housing of West Sumatra is to create an archival application system that can be operated via a computer network, with the aim of increasing the acceleration of the search service process for an archive. This research is: 1) To find out what are the obstacles faced in the archive management system in the General Bureau at the Secretariat General of the Ministry of Public Works and Public Housing of West Sumatra; 2) To find out what are the efforts made to overcome the obstacles in the archive management system in the field of the General Bureau at the Secretariat General of the Ministry of Public Works and Public Housing of West Sumatra; 3) To find out what are the efforts made to overcome the obstacles in the archive management system in the field of the General Bureau at the Secretariat General of the Ministry of Public Works and Public Housing of West Sumatra. This type of research is qualitative research. Qualitative research is research that intends to understand the phenomena experienced by research subjects (such as behavior, perception, action, etc.), holistically, and by means of descriptions in the form of words and language, in a specific natural and natural context. by utilizing various natural methods (Moleong, 2012;: 87). Informants are people who are used to provide information about the situation and conditions of the research background. So he continues to have a lot of experience in the research setting. As a team member with kindness, volunteering can provide views of values, attitudes and culture, which are the background for local research (Moleong; 2012: 90). The types of data are primary data and secondary data collected through interviews, observation and library research. The analysis technique used is qualitative analysis. The results of this study indicate that: recording or distribution of archives in the General Bureau of the Secretariat General of the Ministry of Public Works and Public Housing of West Sumatra Province uses several types, namely the Electronic Service Manuscript System (TNDE) and the outgoing mail agenda book. The conclusion that can be drawn is the dynamic archive management system in the field of the General Bureau at the Secretariat General of the Ministry of Public Works and Public Housing of West Sumatra Province in the aspects of creating and receiving archives, storing, maintaining, and shrinking, namely: in terms of creating and receiving archives, they have followed the existing archival provisions The most frequently created and received dynamic archives are correspondence records (letters). The archive storage system used at the General Bureau is the Electronic Service Manuscript Administration (TNDE) system. This TNDE system is so that letter data will be stored in a centralized database management system, making it easy to maintain data. The search for the TNDE system cannot be done automatically in the access feature in the system. For archival maintenance, the implementation of fumigation is carried out twice every year. In the context of shrinking the archives, there is an alternating dynamic archive assessment team. Archive shrinkage is in accordance with the Archive Retention Schedule (JRA), archives that have passed JRA will be immediately destroyed by burning. Suggestions include the implementation of a good archive management system at the Secretariat General of the Ministry of Public Works and Public Housing of West Sumatra, it should be equipped with supporting facilities and infrastructure.